Contributions for the development of a core outcome set to evaluate pulmonary rehabilitation programs in people with COPD - Miranda, Sara Palos Souto de (2018)
Background: Chronic obstructive pulmonary disease (COPD) is currently the fourth major cause of morbidity and mortality worldwide. Pulmonary rehabilitation (PR) is currently recommended as a fundamental intervention for the management of stable COPD. However, its access is very restricted. Although, the potential of improvement has been used as a criterion to determine patients’ access to PR, the response is highly dependent on the outcomes measures used. Moreover, there is still no consensus on the minimum outcomes that should be assessed (Core Outcome Set – COS) in PR. A COS has the potential to improve consistency among trials and lessen the risk of outcome reporting bias, by including outcomes relevant to different stakeholders. Aim: To explore outcomes of PR valued by patients, informal carers (IC) and health professionals (HP). Methods: Semi-structured interviews were conducted with 12 patients (83.3%♂, 70.8±5.2 years, 50.7±17.5 FEV1pp, 27.2±3.9 BMI), 11 IC (18.2%♂, 68.4±7.9 years, 5.3±7.0 years of caregiving) and 10 HP (20%♂, 40.7±14.3 years, 6.7±9.7 years of experience). Data were analysed following a content analysis approach and thematic analysis afterwards with NVivo software. Results: This study generated 44 outcomes to be assessed in PR. Five relevant themes to all stakeholders were generated from the analysis: having a healthy mind in a healthy body; I can(‘t) do it; feeling fulfilled; knowing more, doing better and avoiding doctors and expenses. Although perspectives were mostly consensual among stakeholders, some outcomes (i.e., pulmonary function) were only valued by HP, whereas patients and IC valued PR for its impact on their day-to-day lives and role in the community. Although some participants did not recognize PR effects in key outcomes reported in the literature such as exercise tolerance, all participants reported at least one positive outcome. Conclusions: This study identified a set of outcomes relevant for the different stakeholders involved in PR, that are not consensual. These results could contribute to the development of a future COS for PR in patients with COPD